Pagina de inicio
/
Matemáticas
/
Simplify: 8sqrt (44)+7sqrt (28)-9sqrt (99)+3sqrt (112) A 11sqrt (43)+26sqrt (7) B 43sqrt (11)+7sqrt (26) C -43sqrt (11)+26sqrt (7) D -11sqrt (11)+26sqrt (7)

Problemas

Simplify:
8sqrt (44)+7sqrt (28)-9sqrt (99)+3sqrt (112)
A
11sqrt (43)+26sqrt (7)
B
43sqrt (11)+7sqrt (26)
C
-43sqrt (11)+26sqrt (7)
D
-11sqrt (11)+26sqrt (7)

Simplify: 8sqrt (44)+7sqrt (28)-9sqrt (99)+3sqrt (112) A 11sqrt (43)+26sqrt (7) B 43sqrt (11)+7sqrt (26) C -43sqrt (11)+26sqrt (7) D -11sqrt (11)+26sqrt (7)

Solución

avatar
Cristóbalprofessionell · Tutor durante 6 años
expert verifiedVerificación de expertos
4.2 (211 votos)

Responder

To simplify the expression $8\sqrt{44} + 7\sqrt{28} - 9\sqrt{99} + 3\sqrt{112}$, we need to simplify each square root term individually.<br /><br />First, let's simplify $\sqrt{44}$:<br />$\sqrt{44} = \sqrt{4 \times 11} = \sqrt{4} \times \sqrt{11} = 2\sqrt{11}$<br /><br />Next, let's simplify $\sqrt{28}$:<br />$\sqrt{28} = \sqrt{4 \times 7} = \sqrt{4} \times \sqrt{7} = 2\sqrt{7}$<br /><br />Now, let's simplify $\sqrt{99}$:<br />$\sqrt{99} = \sqrt{9 \times 11} = \sqrt{9} \times \sqrt{11} = 3\sqrt{11}$<br /><br />Finally, let's simplify $\sqrt{112}$:<br />$\sqrt{112} = \sqrt{16 \times 7} = \sqrt{16} \times \sqrt{7} = 4\sqrt{7}$<br /><br />Now, substitute the simplified square roots back into the original expression:<br />$8\sqrt{44} + 7\sqrt{28} - 9\sqrt{99} + 3\sqrt{112} = 8(2\sqrt{11}) + 7(2\sqrt{7}) - 9(3\sqrt{11}) + 3(4\sqrt{7})$<br /><br />Simplify the expression:<br />$= 16\sqrt{11} + 14\sqrt{7} - 27\sqrt{11} + 12\sqrt{7}$<br /><br />Combine like terms:<br />$= (16 - 27)\sqrt{11} + (14 + 12)\sqrt{7}$<br />$= -11\sqrt{11} + 26\sqrt{7}$<br /><br />Therefore, the simplified expression is $-11\sqrt{11} + 26\sqrt{7}$, which corresponds to option D.
Haz clic para calificar: